The problem of salinization activation in soils of the south of Eastern Siberia and Mongolia in connection with climate aridization - E. I. Pankova; G. I. Chernousenko (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
The influence of climate aridization on soil salinity in the basins of the south of Eastern Siberia and Mongolia is considered in the article. The data characterizing the climate aridity of the basins of the south of Eastern Siberia over 50 years are analyzed. In the south of Eastern Siberia from 1955 to 2015, the increase in air temperature was higher than in the whole world. In the basins of Tuva, the increase in air temperature was 2.5–3.7 оС; in the Minusinsk depression – 1.7–2.8 оС, in the basins of Buryatia – 1.5–1.8 оС; the coefficient of determination for moving averages over 20 years (R2) was 0.9–0.95, the changes are significant – Student's criterion 19–35. Changes in the aridity coefficient were in the range of 0.02–0.14; according to the Student criterion, they were significant (t = 7.4 – -22), while a decrease in aridization was observed in the Minusinsk depression and its growth in other regions. Thus, in general, for the studied regions, the multidirectionality of the processes of climate aridization has been ascertained. In the Minusinsk depression, despite a slight decrease in aridization, category changes (according to the classification of Lobova et al., 1977) did not occur during this period, the territory remained in the arid and subarid categories. Despite the increase in climate aridization in the basins of Tuva and Buryatia, most of them also did not show a tendency to more arid category. Nevertheless, in a number of hollows in the south of Eastern Siberia, an increase in aridization with a transition to a more arid category was observed. This applies to the Eravnensky and Barguzinsky basins of Buryatia, which switched from weakly arid to subarid, as well as to the Ubsunur basin of Tuva, which turned from arid to strongly arid. For the basins of the south of Eastern Siberia, where climate aridization was recorded, the question arose about the possible activation of the process of soil salinization. To solve this problem, materials were collected on soil salinity in the arid regions of Mongolia. It was found that an increase in climate aridity even in the extreme arid deserts of the Gobi, where parent rocks are not saline, under automorphic conditions, the soil is practically not saline (the amount of salts does not exceed 0.1%). In areas where saline Cretaceous-Paleogene red sediments are spread, automorphic soils are saline, and the amount of salts may exceed 2.5%. Thus, in extremely arid climatic conditions, salinization of automorphic soils can range from non-saline to highly saline. Under the hydromorphic conditions of the basins of the south of Eastern Siberia, as well as in Mongolia, climate aridization inevitably leads to an intensification of the salt accumulation process, therefore, in the basins of Tuva and Buryatia experiencing climate aridization, a process of soil salinization in hydromorphic landscapes should be expected.